Urgensi Desain Collaborative Governance dalam Pemilu dan Pilkada: Studi Kasus Malpraktik Elektoral Tahapan Pencalonan Pemilu DPRD Provinsi NTT dan Pilkada Sabu Raijua - Silvester Sili Teka (Jurnal Adhyasta Pemilu, 2021)
This paper offers collaborative governance as a concept of strengthening collaboration between institutions in the implementation of elections and local elections, namely by examining the phenomenon of electoral malpractice cases in the nomination stages in the 2019 NTT Provincial DPRD Election and the 2020 Sabu Raijua Regent and Deputy Regent Election. This study uses qualitative research methods descriptive with analysis techniques and data collection based on primary data and secondary data and literature study. The study results based on the case studies in this paper found that the concept of collaborative governance was able to overcome the weakness of the rules and the limitations of the authority of the election organizers at the election and regional head elections. This is evidenced by the potential for electoral malpractice in the nomination stage, which lies in the weakness of the rules for the verification mechanism for only administrative candidate requirements, so they are prone to be manipulated by candidates. At the same time, it is known that the validity and correctness of candidate requirements documents is the domain of authority of institutions outside the Organizing Institution Election (LPP). Therefore, collaboration and synergy between election organizers and stakeholders are needed based on collaborative governance to prevent electoral malpractice. The collaborative governance approach encourages collaborative problem solving involving stakeholders based on mutual trust and commitment and is oriented towards consensus. The cycle of collaborative governance that must be passed is face-to-face dialogue, trust-building, commitment to the process, shared understanding, and intermediate outcomes. Furthermore, legal norms are needed to regulate inter-institutional cooperation for election organizers to strengthen collaborative governance.